Tajikistan : Overview of Tobacco Use, Tobacco Control Legislation, and Taxation - World Bank Group (World Bank, Washington, DC, 2019)
Smoking prevalence Tajikistan remains rather moderate. According to the Global Adult Tobacco Survey (GATS) conducted in 2016, smokers constitute 6.3 percent of the adult population of Tajikistan. However, 12.5 percent of study participants reported consuming smokeless tobacco (nasway). Tajikistan joined the Framework Convention on Tobacco Control (WHO FCTC) in 2013. Tobacco control legislation was adopted in 2010 and amended in 2017 in line with the FCTC guidelines. The new pictorial health warnings should cover at least 75 percent of the surface on both largest sides of the packs. The amended law bans point-of-sale advertising. However, tobacco excise rates in Tajikistan were very low, and tobacco affordability was growing. In July 2018, the cigarette excise rates were increased almost 10-fold, but cigarette prices increased in 2018 only by 19 percent as the excise is still very low in monetary terms (about 0.25 USD per pack of 20 cigarettes). Cigarette taxes and prices in Tajikistan are still lower than in neighboring countries, and cigarette smuggling out of Tajikistan exceeds cigarette smuggling into the country. Special policies aiming to discourage nasway use and related surveillance activities should be implemented in Tajikistan, while the introduction of excise or other taxes for such a home-made product can hardly produce substantial benefits. Tobacco use surveillance and monitoring should be developed in the country including publicly available information on sales of tobacco products, as well as their prices, excise revenue, and other economic indicators. Tajikistan has a great potential to increase tobacco excise rates in 2019 and in the following years, as well as to contribute to health objectives related to the reducing tobacco use. The greater the excise tax increase, the larger both the reduction in tobacco consumption and tobacco excise revenue growth will be.